The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3847/1538-4357/ab064f
|View full text |Cite
|
Sign up to set email alerts
|

Chandra Detection of Intracluster X-Ray Sources in Fornax

Abstract: Based on archival Chandra observations with a total exposure of 1.3 Ms, we study Xray point sources in the Fornax cluster of galaxies, with the primary aim of searching for intra-cluster X-ray source populations. We detect 1177 point sources out to a projected radius of ∼30 arcmin (∼180 kpc) from the cluster center and down to a limiting 0.5-8 keV luminosity of ∼ 3 × 10 37 erg s −1 . We construct source surface density profile, after excluding sources associated with foreground stars, known globular clusters, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 76 publications
3
36
0
Order By: Relevance
“…These authors found that the average distance between ICL and DM is around 25 kpc within the first 140 kpc from the center, making the ICL a more reliable tracer of the mass distribution than, e.g., X-ray emissions (X-ray emission, however, has been important as well for the detection of the ICL. Indeed, some studies on Virgo (e.g., [94]) and Fornax (e.g., [95]) have shown that the X-ray band can be a sensitive and independent way to trace the ICL, although, given the current amount of data available, these studies would be limited to near groups/clusters.). A similar conclusion has been reached by other authors (e.g., [85][86][87][88]) with different methods.…”
Section: Introductionmentioning
confidence: 99%
“…These authors found that the average distance between ICL and DM is around 25 kpc within the first 140 kpc from the center, making the ICL a more reliable tracer of the mass distribution than, e.g., X-ray emissions (X-ray emission, however, has been important as well for the detection of the ICL. Indeed, some studies on Virgo (e.g., [94]) and Fornax (e.g., [95]) have shown that the X-ray band can be a sensitive and independent way to trace the ICL, although, given the current amount of data available, these studies would be limited to near groups/clusters.). A similar conclusion has been reached by other authors (e.g., [85][86][87][88]) with different methods.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting prospect is the detection of intracluster X-ray sources in Virgo and Fornax [121,122], likely associated with X-ray binaries in the ICL population [123]. This will not only open a new, and independent, window on the study of the ICL in other wavelengths rather than the optical or near-infrared, but could also provide constraints on progenitors of this light (their initial mass [124]).…”
Section: To Go Beyondmentioning
confidence: 99%
“…We performed X-ray source detection in the 0.5-2, 2-8, and 0.5-8 keV bands for each observation using the CIAO tool wavdetect. We follow the method described in Hou et al (2017) and Jin et al (2019). We have supplied the exposure and 50% enclosed count fraction (ECF) PSF maps and have adopted a false detection probability of P ≤ 10 −6 .…”
Section: X-ray Source Detectionmentioning
confidence: 99%